(3GdJfejI GdeSJOGeI hJWHjbGJgG GdJQHhjI (B/s - (3GdRgQGfj, eYLH Hf CMeO eYLHs ((3YeGf, GdCQOf (B:s (3OGQ cfhR GdeYQaI ddfTQ hGdJhRjY,s, 2016)
(3jJfGhd GdcJGH GdJfejI GdeSJOGeI ceHOC ESdGej CUjd heaghe MOjK hGSY GdJOGhd heJYOO GdESJNOGeGJ hGdeYGfj, agj VQhQI edMI heWdH YUQj Jdbi EgJeGeG YGdejG, djS abW Ydi UYjO GdeLJeYGJ GdYQHjI hGdESdGejI aMSH hEfeG Ydi eSJhi GdeLJeY GdEfSGfj ccd hPdc HEYJHGQgG bVjI CNdGbjI hEfSGfjI HbOQ eG gj bVjI JfehjI hHjFjI, hefgL MjGI hYde jbhe Ydi GdJacjQ HWQjbI TehdjI JcGedjI fMh QDjI LOjOI ddJZdH Ydi CReI GdJfejI aj GdYGde hGdfghV HGdCQV hehGQOgG hESJOGeI GdHTQ hJfejI bOQGJge hJdHjI EMJjGLGJge GdMGdjI hGdeSJbHdjI(B. s
(3HHdjhLQGajI (B: 409-432.s
Keywords: (3GdJQHjIs -- (3LhGfH GbJUGOjIs; (3GdJfejI GdeSJOGeIs -- (3GdJfejI GdGbJUGOjIs; (3GdJWhQs